2015
DOI: 10.1111/1346-8138.13094
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine but not osteoprotegerin correlates with disease severity in patients with moderate‐to‐severe psoriasis undergoing anti‐tumor necrosis factor‐α therapy

Abstract: Patients with psoriasis, in particular those with severe disease, have an increased risk of cardiovascular (CV) events compared with the general population. The aim of the present study is to determine whether correlation between asymmetric dimethylarginine (ADMA) and osteoprotegerin (OPG), two biomarkers associated with CV disease, and disease severity may exist in patients with moderate-to-severe psoriasis. We also aimed to establish if baseline serum levels of these two biomarkers could correlate with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Pina et al . have described asymmetric dimethylarginine (ADMA) and osteoprotegerin (OPG), two biomarkers associated with CVD in 29 patients with moderate to severe psoriasis, and they found that that ADMA correlates with the severity of psoriasis . In another study, the authors investigated the correlation of leptin and resistin with metabolic syndrome features and disease severity in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pina et al . have described asymmetric dimethylarginine (ADMA) and osteoprotegerin (OPG), two biomarkers associated with CVD in 29 patients with moderate to severe psoriasis, and they found that that ADMA correlates with the severity of psoriasis . In another study, the authors investigated the correlation of leptin and resistin with metabolic syndrome features and disease severity in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
“…psoriasis, and they found that that ADMA correlates with the severity of psoriasis. 24 In another study, the authors investigated the correlation of leptin and resistin with metabolic syndrome features and disease severity in psoriasis patients. They showed that leptin correlates with metabolic syndrome and inflammation, whereas resistin correlates with inflammation and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In a six-month prospective study, carotid arterial stiffness in patients with psoriasis was significantly improved by anti-TNF-α therapy (71). In addition, other markers for systemic inflammation such as asymmetric dimethylarginine, red blood cell distribution width, the neutrophil-to-lymphocyte ratio, and the platelet-to-lymphocyte ratio, have proven to be upregulated in psoriatic patients (72-74). …”
Section: Pathophysiology Of Comorbiditymentioning
confidence: 99%
“…Additionally, psoriasis has significant co‐morbidity with systemic inflammatory diseases, such as cardiovascular diseases and metabolic syndrome, and these conditions are currently receiving increasing attention . In parallel, a plethora of inflammatory biomarkers are elevated in psoriasis …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] In parallel, a plethora of inflammatory biomarkers are elevated in psoriasis. [28][29][30][31][32] In addition to these co-morbid diseases that have a systemic inflammatory nature, 33 psoriasis presents with autoimmune aspects and co-exists with a variety of autoimmune disorders. [34][35][36][37][38][39] In this article, we summarize recent topics on autoimmunity and autoimmune co-morbidities in psoriasis.…”
Section: Introductionmentioning
confidence: 99%